Hrup kot okoljski problem - Cigale, Dejan (Geografski obzornik, 2005)
Surveys show the growing importance of noise issue also in Slovenia. More than 30 % of population are over-burdoned by traffic noise. Expertise on Ljubljana indicates that for 36 % of population noise represents a huge disturbance though a quarter is indifferent. The issue on noise over-burdening in settlements is partly solved by new highways and detours, but the problem is getting bigger due to increased traffic.
Keywords: Ljubljana; onesnaževanje okolja; hrup; environmental protection; varstvo okolja